Hubungan Pengetahuan Tentang Gizi dan Praktik Diet dengan Kejadian Hipertensi Akibat Komplikasi Diabetes Melitus Tipe 2 - Taufik Hidayat (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Type 2 diabetes mellitus is a metabolic disease with characteristics of hyperglycemia that occurs due to insulin resistance and causes dysfunction or damage to various organs. Hypertension is one of the diseases caused by complications of type 2 diabetes mellitus. Nutritional knowledge and dietary practices are an integral component of the prevention of complications of type 2 diabetes mellitus. This study aims to analyze the relationship between nutritional knowledge and dietary practices with the incidence of hypertension due to complications of type 2 diabetes mellitus. This type of research is quantitative with a correlational analytic descriptive design using a cross-sectional approach. The population of this study was all type 2 diabetes mellitus patients who were treated at H. Sahudin Hospital Kutacane with a simple random sampling technique. Determination of the number of samples using the Slovin formula obtained 188 patients. The results of data analysis found that there was a relationship between knowledge about nutrition and dietary practices with the incidence of hypertension due to complications of type 2 diabetes mellitus, p-value 0.014. Based on the results of the study, it can be suggested that health workers can provide nutrition education to prevent ongoing complications in type 2 DM.